AGGRESSION ON HAEMODIALYSIS UNITS: A MIXED METHOD STUDY. Issue 3 (16th July 2014) - Jones, Julia; Nijman, Henk; Ross, Jamie; Ashman, Neil; Callaghan, Patrick
SUMMARY Background Aggression on haemodialysis units is a growing problem internationally that has received little research attention to date. Aggressive behaviour by patients or their relatives can compromise the safety and well‐being of staff and other patients sharing a haemodialysis session. Objectives The objectives of the study were twofold: First, to identify the prevalance and nature of aggression on haemodialysis units; and second, to investigate factors that contribute to aggressive behaviour on haemodialysis units. Design and Methods A cross‐sectional, sequential mixed method research design was adopted, with two research methods utilised. Incidents of aggressive behaviour were recorded over a 12‐month period, using a renal version of the Staff Observation Aggression Scale. Six months after the incident data collection had commenced, semi‐structured qualitative interviews were conducted with 29 multidisciplinary members of staff. Results Over 12 months, 74 aggressive incidents were recorded. The majority of incidents involved verbal aggression, and the perpetrators were a minority of patients, relatives and staff. Two patients were responsible for 38% of all incidents; both patients had mental health problems. Distinct temporal patterns to the aggressive behaviour were observed according to the day of the week and time of day. Conclusion This study demonstrates that aggression is a significant problem on haemodialysis units, with verbal aggression most prevalent. The temporal patterns to aggression observed are related to the uniqueness of the haemodialysis setting, with a distinctly different treatment environment compared with other healthcare settings.